The Role of Job Satisfaction in Linking Work Environment and Motivation to Employee Performance: Evidence from an Electrical and Mechanical Contracting Company - Hendra Sanjaya Kusno; Sisca Santika; Ranita Ramadhani; Danar Retno Sari (MEC-J (Management and Economics Journal), 2026)
Numerous studies have examined the relationships among work environment, work motivation, job satisfaction, and employee performance, empirical findings remain inconsistent, particularly regarding the mediating role of job satisfaction. Moreover, research focusing on electro-mechanical contracting companies operating in project-based and high-risk environments remains limited. This study aims to analyze the influence of work environment and work motivation on employee performance, with job satisfaction as a mediating variable. The research was conducted at PT. XXX involving 41 employees using a saturated sampling technique. Data were analyzed using Structural Equation Modeling, Partial Least Squares (SEM-PLS) with bootstrapping to examine direct and indirect effects. The results indicate that work environment and work motivation significantly influence job satisfaction, and job satisfaction partially mediates their relationship with employee performance. However, the direct effects remain significant, suggesting complementary rather than full mediation. The findings reveal that in project-based organizational contexts, employee performance is shaped not only by psychological satisfaction but also by structural and operational demands. Theoretically, this study extends Herzberg’s Two-Factor Theory and is further supported by Self-Determination Theory by demonstrating that satisfaction functions as a psychological transmission mechanism rather than the sole determinant of performance. Practically, the findings highlight the importance of simultaneously strengthening structural work systems and motivational strategies to enhance employee performance.